2004
DOI: 10.1111/j.0953-816x.2004.03370.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting nicotinic modulation of GABAergic synaptic transmission in the rat nucleus accumbens associated with behavioural sensitization to amphetamine

Abstract: A robust increase in dopaminergic transmission in the nucleus accumbens (NAc) shell has been reported to be consistently associated with the long-term expression of behavioural sensitization to drugs of abuse. However, little is known about how this affects the neuronal network of the NAc. We made cellular recordings in NAc slices of saline- and amphetamine-pretreated adult rats and found that expression of behavioural sensitization was associated with long-lasting changes in the basal firing pattern of cholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…The putative presence of cholinergic interneurons in the PFC introduces the possibility of nicotine-induced ACh release independent of release from cholinergic terminals that originate from lower brain areas. Because the PFC is implicated in behavioral sensitization (see below), intrinsic properties of cholinergic interneurons and ACh release in the PFC could also be modified during behavioral sensitization, as we found in the NAc (de Rover et al 2004). Figure 1a shows a putative rodent PFC circuitry and locations of nAChRs as found in the PFC (Alkondon et al 2000;Lambe et al 2003;Metherate 2004) and other cortical areas.…”
Section: Location Of Nicotinic Receptors In Hippocampus Amygdala Anmentioning
confidence: 86%
See 1 more Smart Citation
“…The putative presence of cholinergic interneurons in the PFC introduces the possibility of nicotine-induced ACh release independent of release from cholinergic terminals that originate from lower brain areas. Because the PFC is implicated in behavioral sensitization (see below), intrinsic properties of cholinergic interneurons and ACh release in the PFC could also be modified during behavioral sensitization, as we found in the NAc (de Rover et al 2004). Figure 1a shows a putative rodent PFC circuitry and locations of nAChRs as found in the PFC (Alkondon et al 2000;Lambe et al 2003;Metherate 2004) and other cortical areas.…”
Section: Location Of Nicotinic Receptors In Hippocampus Amygdala Anmentioning
confidence: 86%
“…Cholinergic interneurons in the nucleus accumbens (NAc) can affect GABAergic transmission within the NAc itself via nAChR activation (de Rover et al 2002). In addition, these cholinergic interneurons could be important in lasting changes in microcircuitries that affect animal behavior, because their intrinsic firing properties are altered during behavioral sensitization to amphetamine (de Rover et al 2004). Furthermore, it is known from immunohistochemical data that a small fraction of bipolar interneurons in layer II/III of the sensory and motor cortices are cholinergic (Houser et al 1985).…”
Section: Location Of Nicotinic Receptors In Hippocampus Amygdala Anmentioning
confidence: 99%
“…The first is sensitization, both locomotor (Ksir et al, 1985;de Rover et al, 2004) and cognitive (Rezvani and Levin, 2001;Dani and Bertrand, 2007). In the human context, cognitive sensitization is epitomized by smokers' reports that they think better when they smoke; this anecdotal observation is confirmed by data that smokers who smoke nicotine cigarettes (but not nicotine-free cigarettes) display certain cognitive enhancements (Rusted and Warburton, 1992;Rusted et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that repeated exposures to nicotine enhance behavioral sensitization to amphetamine (de Rover et al 2004), while blockade of nAChRs prevents the induction of behavioral sensitization to amphetamine or cocaine (Schoffelmeer et al 2002).…”
Section: Introductionmentioning
confidence: 99%